PENYELESAIAN SENGKETA UPAH YANG TIDAK DIBAYARKAN KEPADA PEKERJA PADA MASA PANDEMI COVID-19 - Geraldo Khekar Gabriel Simatupang (2022)
The Covid-19 pandemic is a disease outbreak that has hit almost all corners of the world, its rapid spread is a factor why this virus quickly spreads throughout the world, including Indonesia. The impact caused by Covid-19 has caused Indonesia to make policies to minimize the spread of Covid-19 by suppressing activities outside the home. The impact is that many companies experience losses due to decreased income, with this incident the company did not pay employee wages unilaterally without any agreement that occurred between employers and workers/labor. With this dispute, it can be resolved in various ways and there is an authorized agency to resolve disputes that occur and see the sanctions received by entrepreneurs. In this paper, using empirical juridical research where the authors search for data by going directly to the field. Settlement that can be done to resolve disputes that occur here can be through the mechanism of Bipartite Negotiations, Settlement Through Labor Inspectors and Investigations ending with a judge's decision.